Occupational Sorting and Wage Gaps of Refugees - Christopher F. Baum; Hans Lööf; Andreas Stephan; Klaus F. Zimmermann (Global Labor Organization (GLO), 2020)
Refugee workers start low and adjust slowly to the wages of comparable natives. The innovative approach in this study using unique Swedish employeremployee data shows that the observed wage gap between established refugees and comparable natives is mainly caused by occupational sorting into cognitive and manual tasks. Within occupations, it can be largely explained by differences in work experience. The identification strategy relies on a control group of matched natives with the same characteristics as the refugees, using panel data for 2003–2013 to capture unobserved heterogeneity.
Keywords: C23; F22; J24; J6; O15; 330; refugees; wage earnings gap; Blinder–Oaxaca decomposition; employer-employee data; coarsened exact matching; correlated random effects model